Urgensi Kafa'ah Dalam Mempertahankan Keluarga Dari Campur Tangan Orang Tua - Jufri; A. Natsir, Andi Fadhilah; Laelah, Ariesthina (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2023)
This paper focuses on building family resilience from third-party intervention, which in this paper is parents/in-laws. The definition of a happy family is a family filled with mutual love, affection, protection and respect. However, the definition of a happy family above will not be achieved without the reconception of love and balance from the beginning and beyond as an effort to fortify the intervention of parents/in-laws. The application of the concept of harmony and balance in this study is one of the responsive efforts to create a stronghold of family resilience against the problematic intervention of parents/in-laws in the household life of their children/in-laws. This type of library research uses the descriptive-analytic method to obtain and analyze all the data obtained. The results of this study explain that it takes hard work and support between husband and wife to prevent third-party intervention as a trigger for household breakdown. Factors that influence parents to interfere in their children's households, namely: living in the same house, still close to the place of residence, lack of income from the son-in-law/child (economy), lack of affection from parents, lack of communication with in-laws and incompatibility between parents/in-laws and children/children in law. Anticipating the above, as an effort to build family resilience from third-party interference is to apply the concept of love and balance that each party can understand and good communication based on faith so that it can present an attitude of love and understanding and ultimately family harmony can be formed.